National and international private bankers and the building of the Italian credit and financial system during Italian unification - Marina Romani; Luciano Maffi (The Journal of European Economic History (JEEH), 2023)
The Italian credit and financial system was the result of progressive developments that accelerated during the process of Italian unification. Our essay analyses the role of local private bankers in modernizing the economic and financial system of the country and the way in which the gradual increase of social capital - an asset consisting of interpersonal relations - fostered cooperation among Italian bankers in a period in which it was easier to create trust in people rather than in institutions. Using documents from the Archives General du Travail (Roubaix) we have sought to demonstrate that the close relationship between Italian private bankers and the international haute banque permitted both easier placement of Italian public bonds on the local market and the progressive integration of the national financial market. Italian public debt thus became one of the means to create the national state.
Keywords: 330; Bank; Financial market; National unity; History; Italy; Bank; Finanzmarkt; Nationale Einheit; Geschichte; Italien